Multicystic Benign Cystic Mesothelioma Presenting as a Pelvic Mass - Mazdak Momeni; Elena Pereira; Gennadiy Grigoryan; Konstantin Zakashansky (Case Reports in Obstetrics and Gynecology)
Background. Benign cystic mesothelioma (BCM) is a rare tumor that arises from the abdominal peritoneum with a predilection to the pelvic peritoneum. For this reason, it can often mimic gynecologic malignancies. Case. A 47-year-old perimenopausal female presented reporting several weeks of abdominal distention associated with abdominal tenderness and constipation. Computed tomography revealed a 24 cm multiloculated pelvic mass, and tumor markers were notable for an elevated CA-125. The patient was taken to the operating room for an exploratory laparotomy, total abdominal hysterectomy, bilateral salpingoophorectomy, and removal of pelvic mass. Final pathologic evaluation revealed a benign cystic mesothelioma. Conclusion. Classically these tumors present as large multicystic masses with thin-walled septations and on preoperative evaluation BCM can mimic many different disease entities including ovarian malignancies and cystic lymphangioma. Often diagnosis can only be made at time of surgery.